Chapter 7 Listening to the talkies Atarashiki tsuchi's (1937) acoustic construction of Japan for western consumption - Haukamp, Iris (Taylor & Francis, 2023)
This chapter examines the choices made regarding film sound-music, sound, and noise-for creating a target-oriented image of Japan for the anticipated German audience in Atarashiki tsuchi (New Earth aka Die Tochter des Samurai, 1937). This Japanese-German co-produced film, produced entirely in Japan, with a binational cast and crew and in a highly politicised context, was supposed to showcase both contemporary Japan and its film industry to the world. The use of sound for the creation of meaning in this film has been largely overlooked in favour of its strong visuals. However, an analysis of selected sections shows that the major messages are actually encoded on the soundtrack and that a focus on sound provides a potent tool for revealing the underlying imbalance regarding cultural power and authority at work in the project.